Enhancing The Seventh Grade Students’ Speaking Achievement of SMPN 38 Palembang Through Scaffolding Talk Technique - Nisfu Laili; Nike Angraini (Universitas Indo Global Mandiri, 2018)
AbstractThe purposes of the study were to find out whether or not Scaffolding Talk Technique was effective to enhance the speaking achievement and speaking aspects of the seventh grade students of SMPN 38 Palembang and to find out whether or not there was significant difference on speaking achievement between the students who were taught by using Scaffolding Talk Technique and those who were not. In order to achieve the purposes of the study, the writer has conducted an experimental research design. Besides, 60 students were selected by using purposive sampling to be the experimental and control group. The experimental group was taught through Scaffolding Talk technique carried out for 2 months. The results of the achievement test were statistically analyzed by using paired samples t-test and independent samples t-test. The mean score of experimental group in pre-test was (11.67) enhanced to (15.37) in post-test. Furthermore, the speaking aspects enhanced for each aspects. The mean score of comprehension in pre-test was (2.83) enhanced to (3.03), Vocabulary (2.80) enhanced to (3.03), Pronunciation (2.27) enhanced to (2.93), Grammar (1.93) enhanced to (2.90), and fluency (1.83) enhanced to (2.73). Moreover, the significant difference of post-test both of groups was 0.01. In short, Scaffolding Talk Technique was effective to enhance the speaking achievement and speaking aspects. Additionally, there was the significant difference on speaking achievement between the students who were taught by using Scaffolding Talk Technique and those who were not. Furthermore, during teaching and learning process, students were more active in speaking class and more confident to perform or do the task independently without any help from teacher or peer.Keywords : teaching, scaffolding talk technique, speaking achievement. AbstrakTujuan penelitian ini adalah untuk mengetahui apakah Scaffolding Talk Technique efektif untuk meningkatkan prestasi berbicara dan aspek berbicara siswa kelas tujuh SMPN 38 Palembang dan untuk mengetahui apakah ada perbedaan yang signifikan pada prestasi berbicara antara siswa yang diajar dengan menggunakan Teknik Bicara Scaffolding dan mereka yang tidak. Untuk mencapai tujuan penelitian, penulis telah melakukan desain penelitian eksperimental. Selain itu, 60 siswa dipilih dengan menggunakan purposive sampling menjadi kelompok eksperimen dan kontrol. Kelompok eksperimen diajarkan melalui teknik Scaffolding Talk yang dilakukan selama 2 bulan. Hasil tes prestasi dianalisis secara statistik dengan menggunakan paired samples t-test dan independent samples t-test. Skor rata-rata dari kelompok eksperimen dalam pre-test adalah (11,67) ditingkatkan menjadi (15,37) dalam post-test. Selanjutnya, aspek berbicara ditingkatkan untuk setiap aspek. Skor rata-rata pemahaman dalam pre-test adalah (2,83) ditingkatkan ke (3,03), Vocabulary (2,80) ditingkatkan ke (3,03), Pelafalan (2,27) ditingkatkan menjadi (2,93), Grammar (1,93) ditingkatkan menjadi (2,90), dan kefasihan (1,83) ditingkatkan ke (2,73). Selain itu, perbedaan signifikan dari post-test kedua kelompok adalah 0,01. Singkatnya, Teknik Scaffolding Talk efektif untuk meningkatkan prestasi berbicara dan aspek berbicara. Selain itu, ada perbedaan yang signifikan pada prestasi berbicara antara siswa yang diajar dengan menggunakan Teknik Bicara Scaffolding dan mereka yang tidak. Selanjutnya, selama proses belajar mengajar, siswa lebih aktif di kelas berbicara dan lebih percaya diri untuk melakukan atau melakukan tugas secara mandiri tanpa bantuan dari guru atau rekan.Kata kunci : mengajar, teknik berbicara perancah, berbicara prestasi.